Modulation of cognitive processing by emotional valence studied through event-related potentials in humans - Delplanque, Sylvain; Lavoie, Marc E.; Hot, Pascal; Silvert, Laetitia; Sequeira, Henrique (Neuroscience letters, 2004)
This experiment investigated whether the emotional content of a stimulus could modulate its cognitive processing. Particularly, we focused on the influence of the valence dimension on the cognitive processing triggered by a non emotional oddball task. To this end, event-related potentials (ERPs) were recorded from 25 sites during a visual oddball paradigm. Three sets of pictures (unpleasant, neutral and pleasant) with low arousal values served as rare target items. Subjects were simply asked to realize a standard/target categorization task, irrespective of the picture valence. A temporal principal component analysis allowed us to identify several evoked components (i.e. P1, P2, N2, P3a and P3b). Emotional effects observed on P1, P2 and P3b showed that the valence content of the stimulus modulates the cognitive processes at several points in the information processing stream.